The seasonal variations of respiratory syncytial virus infections in Turkey: a 2-year epidemiological study - Turkish Neonatal Society (The Turkish Journal of Pediatrics, 2012)
Respiratory syncytial virus (RSV) infections may cause severe respiratory diseases, particularly in infants and young children. In order to determine the timing of prophylaxis, the seasonal variations of RSV had to be determined. We report the climate-related results of an epidemiological study conducted in 32 hospitals of Turkey between May 2008 and September 2010, on children < 2 years of age hospitalized with lower respiratory tract infection. Information on socio-demographics, medical history, risk factors for RSV, diagnosis and severity of RSV, and hospitalization was recorded. RSV Respi-strip test kits were used to detect RSV. The meteorological data, including average monthly temperature, relative humidity (RH) and rainfalls of all cities were obtained, and the correlations between meteorological variables and RSV positivity were determined. Informed consents were obtained before the study. Overall, 3,464 children (61.9% boys), with a mean age of 6.4 months, were evaluated. RSV positivity was 16.9%. RSV peaked in January and March, in the first and second RSV seasons, respectively. When Turkey was evaluated as a whole, RSV was positively correlated with RH (p < 0.001, R = 0.627) and rainfalls (p = 0.001, R = 0.572), and was negatively correlated with temperature (p < 0.001, R = -0.778). However, when the regions were evaluated separately, the rainfalls had a negative correlation with RSV activity in the Black Sea and East Anatolian regions. The current study shows the seasonal variation of RSV infections in Turkey in two consecutive RSV seasons. Country-specific viral surveillance systems are required to detect respiratory virus activities and to implement health care strategies.